Application of AHP (Analytical Hierarchy Process) Method in Inventory Control at PT. Sumber Rezeki Bersama - Eko Sumarsono (Institute of Computer Science (IOCS), 2021)
Controlling the amount of inventory value is not an easy thing for companies, starting from recording the purchase price of goods, determining prices to presenting these inventories into financial statements. To facilitate inventory control, a decision support system is needed that aims to simplify the inventory control process which is expected to help the problems that exist in the company. The same thing is needed by PT. Source of Mutual Sustenance. This private company engaged in the distribution of food products also needs a decision support system that can control the inventory of goods so as to facilitate the process of controlling inventory. Previously, inventory at PT. Sumber Rezeki Bersama experienced problems where the company did not prioritize ordering goods, especially those with the highest sales. So that when there are many messages from consumers for these goods, the company cannot fulfill orders on time, given the stock of goods that are not always available (because they are not prioritized).